2021
DOI: 10.1007/s00270-021-03014-w
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Embolization Using N-Butyl Cyanoacrylate-Glue: What Impact Does a Central Vascular Plug Have?

Abstract: Purpose To examine if the addition of a central vascular plug (CVP) to portal vein embolization (PVE) with N-butyl cyanoacrylate-glue (NBCA) increases future liver remnant (FLR) growth. Material and Methods This is a single-center retrospective study of 115 consecutive patients with colorectal liver metastases undergoing PVE in 2013–2019. All patients were embolized with NBCA as the main embolic agent. In 2017–2019 NBCA was combined with a CVP in the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In a retrospective study comparing PVE performed using NBCA alone versus PVE performed using NBCA with AVP assistance, NBCA plus AVP assistance was associated with greater increases in degree of hypertrophy ( p = 0.02) and kinetic growth rate of the FLR ( p = 0.07), as well as reduced fluoroscopy time ( p < 0.01). 32 These results support our hypothesis that the better outcomes seen with NBCA plus AVP assistance are related to the complete embolization of the PV branches and reduced recanalization seen with this technique. AVP assistance may also reduce the need for subsegmental catheterization of PV branches for embolization, leading to reduced procedure and fluoroscopy times and lower contrast requirements.…”
Section: Rationale For Liver Venous Deprivationsupporting
confidence: 81%
See 2 more Smart Citations
“…In a retrospective study comparing PVE performed using NBCA alone versus PVE performed using NBCA with AVP assistance, NBCA plus AVP assistance was associated with greater increases in degree of hypertrophy ( p = 0.02) and kinetic growth rate of the FLR ( p = 0.07), as well as reduced fluoroscopy time ( p < 0.01). 32 These results support our hypothesis that the better outcomes seen with NBCA plus AVP assistance are related to the complete embolization of the PV branches and reduced recanalization seen with this technique. AVP assistance may also reduce the need for subsegmental catheterization of PV branches for embolization, leading to reduced procedure and fluoroscopy times and lower contrast requirements.…”
Section: Rationale For Liver Venous Deprivationsupporting
confidence: 81%
“…AVP assistance may also reduce the need for subsegmental catheterization of PV branches for embolization, leading to reduced procedure and fluoroscopy times and lower contrast requirements. 32,33 Liver Venous Deprivation Technique…”
Section: Rationale For Liver Venous Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients in this study also underwent PVE with N-butyl cyanoacrylate glue with varied hypertrophy rates. Some studies have demonstrated that the addition of a central vascular plug or coil in PVE alone is associated with increased hypertrophy rates which may be related to revascularization of the portal vein 38 . Therefore, the technique for PVE used in these studies may be associated with an inferior hypertrophy than more current techniques; however, the technique for PVE was the same for the DVE and PVE groups of each study included.…”
Section: Discussionmentioning
confidence: 99%
“…[3a] However, these products are generally associated with serious limitations: Onyx™ is a popular catheter-injectable embolic agent based on ethylene(vinyl alcohol) (EVOH) dissolved in dimethyl sulfoxide (DMSO), which induces cytotoxicity at the injection site. [4] Histoacryl®, another embolic agent based on adhesive n-butyl cyanoacrylates (NBCAs), [5] suffers from catheter clogging (due to its uncontrollable curing), exothermic solidification, [6] as well as stiffness mismatch with the surrounding soft tissues. [7] Injectable hydrogels have received enormous attention due to their versatility for integration with minimally invasive platforms, e.g., in transcatheter embolization.…”
Section: Introductionmentioning
confidence: 99%